Novel research on polyamide 11 nanocomposites reinforced by Titania nanoparticle deposited jute fibres - Do, Van Cong; Nguyen , Vu Giang; Tran, Huu Trung; Do, Quang Tham; Nguyen , Thi Thai; Mai, Van Tien; Nguyen , Thi Huong (Vietnam Journal of Science and Technology, 2022)
The combination of jute fibres and polyamide 11 (PA11) to produce full biocomposites is expectance of scientists due to many benefits of both these materials such as high mechanical performances and environmentally friendly behaviors. Unfortunately, there is scarce published research on these bicomposites uptil now. In order to improve the interfacial interaction and adhesion between jute fibres and PA11 resin matrix, an important key in the fabrication of the composites. In this study, a combination of alkaline treatment and Tetraisopropyl orthotitanate (Tip) modification was employed to modify the surface of jute fibres. The deposition or grafting of TiO2 nanoparticles was proved by using Fourier transform infrared (FTIR), scanning electron microscopy (SEM) observations and energy dispersive X-ray spectroscopy (EDS/EDX) analysis. The improvement of the interfacial interaction and adhesion between surface modified jute fibres and PA11 resin as well as high performances (mechanical properties, thermal oxidative and water absorption stability) of obtained biocomposites were also clarified.